Preselection area of arepresentative aerobjological sampling station of a tropical valley - Perdomo de Ponce, Doris; Rull, Valentín; Hernández, Amador; Salgado Labouriau, María (Investigación Clínica, 2013)
In order to search an uniform criteria for sampling aerobiological particles, three sites were selected along the valley of Caracas. The distribution of vegetation, topographical and meteorological parameters were monitored. Pollen and spores were collected at each site during 24 hr at 6 min-intervals with a Rotorod sampler. Pollen counts were similar in all sites and much less abundant than spores. Cladosporium was the most abundant spore and grass pollen represented more than 50% of the pollen grains. Results showed that the three sites could be selected al luitable sampling area for airborne pollen and spores. Nevertheless, we recommend the selection of the most accesible and central site for a long-term sampling.